Analisa Sifat Mekanik Resin Dengan Variasi Komposisi Hardener - Sughiandi, Rachmad; Sudarsono, Sudarsono; Endriatno, Nanang (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
The purpose of this research is to find out the ideal mixture composition in theprocess of making polyester in thermoset polymers, where the composition of this mixture will have high tensile strength and bending strength. This thermosetpolymer is made by mixing polyester resin with hardener, varying between 1 %, 2 %, 4 %, and 7 %. Polyester resins that have been mixed with hardener are poured into the mold. After drying, the polymer is input into the mold to be pressed and curing. After drying, a tensile test specimen and bending test are made. Tensile testing is carried out using the ASTM D 638-02 type 4 standard, and bending testing is carried out with ASTM D709-02 type 4 standard. From the results of testing the tensile strength and bending strength obtained the maximum strength found in the mixture composition of 93:7 % with a value of 30.69 N/mm2 and 70.634 N/mm2 respectively.Keywords: Resin, hardener, tensile strength, bending, polymer